New Straits Times, 02 February 2008 - Sharanjit Singh; Audrey Dermawan (The New Straits Times Press (M) Bhd, 2008)
We have helped the rakyat by putting into place several measures like stepping up enforcement to ensure there is no indiscriminate hike in the prices of goods